Alga Merah (Gracilaria verrucosa) sebagai Bahan Bakto Agar - Kumala, Shirly; Sumarny, Ros; Rachmani, Rum; Ruswita, Atut (Jurnal Farmasi Indonesia, 2013)
The used of bacto agar in microbiological studies increased tremendously, however, up till now, to fullfill its high demant the scientist were stil relying on imported bacto agar eventhough domestic production of bacto agar was as goog and reliable as those produced commercially overseas. The current study we focuseon the production of bacto agar from red algae Gracilaria verrucosa using fell press technique;Â followed by quality analysis of the product. Red algae samples were collected from two different locations (Bekasi and Subang). Quality of the product was tested for its content, acid insoluble as content, overall as content, pH, gel strength and its ability to be use as culture media to culture Escherichia coli and Staphylococcus aureus. Microbiological test was performed via pour plate. The results clearlydemonstrated that red algae sample from Bekasi produced bacto agar that meets the criteria of commercial bacto agar. It has 10.3% water content, 3.9% overall as content, 0.4% acid insoluble as content, pH of 7.3 and gel strength of 600.8-602.8 g/square cm.Keywords : Bacto agar, red Algae, Gracilaria verrucosa, Microbe media